Global Peace Security and Conflict Resolution: An Assessment for Global Economic and Sustainable Development (In Factis Pax: Journal of Peace Education and Social Justice, 2018)
This article is an attempt to assess the various macroeconomic, social, political, environmental and other variables that affect and resolve conflict for attaining global peace and security based upon a critical review of core literature in the field. The article argues in support of the proposition that international trade promotes global peace, security and reduces conflicts. The paper highlights the features of the present Trump administration relating to promoting peace through trade. The limitations of trade have also been highlighted. It is observed that international trade promotes global peace, i.e., attainment of positive peace through inclusive societies and security and reduces the scope of wars and militarized conflict.
Keywords: Global peace; multilateral trade; national security; economic diplomacy; foreign policy